Analisis Nilai-Nilai Kehidupan dalam Cerita Rakyat Daerah Semarang sebagai Penguat Profil Pelajar Pancasila - Rini Indah Sulistyowati; Ganda Januarta; Sofyandanu Setiadi (CV. Aksara Global Akademia, 2025)
The Pancasila Student Profile Strengthening Project (P5) is part of the implementation of the Independent Curriculum, which emphasizes the holistic development of student character. The program's primary objective is to develop students with noble character, global diversity, collaborative spirit, independence, critical thinking, and creativity. One approach to integrating these values is through an appreciation of literary works, particularly folktales. Folktales have great potential as educational media because they contain various life values derived from local wisdom. This research focuses on analyzing the life values contained in folktales from the Semarang region and assessing their relevance in supporting the implementation of P5. Amidst the decline in moral values among students, marked by rampant cases of brawls, drug abuse, bullying, and unethical behavior, utilizing folktales as teaching materials is an alternative solution that is contextual and culturally based. Unfortunately, many local folktales remain largely unknown and underutilized in the learning process. The research method used was a qualitative approach with data analysis techniques modeled after Miles and Huberman. The results of the study indicate seven main values contained in Semarang folklore: aesthetic, religious, social, moral, cultural, educational, and economic. These values not only reflect the social conditions of society in the past but also have strong relevance for shaping the character of today's students. Despite differences in the context of the times, folklore can still be used as an effective learning medium, especially when packaged in a more engaging and modern format, such as digital storytelling, animation, or other interactive media. Therefore, the inclusion of folklore in P5 can bridge the gap between cultural heritage and sustainable character education.